Heterogeneous Sequence Node of Associated Coverage Algorithm in Wireless Sensor Network - Zeyu Sun; Zhaohui Chen (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In the premise of meeting the quality of network service, how to effectively cover the monitoring area and how to prolong the network lifetime has become one of the wireless sensor network researches. Therefore, this paper proposes heterogeneous nodes based on association covering algorithm. On one hand, this algorithm is handled through the Poisson model of structure joint probability density formula and it is also based on the node density formula to establish sensor node in the monitoring area in order to efficiently cover the focused target. On the other hand, it updates through the node's own state scheduling mechanism and converts neighbor nodes dynamically about matching scheduling, which can balance the monitoring area sensor node residual energy and node energy consumption. Therefore it can achieve the purpose of prolonging network lifetime .Finally, the simulation results show that the algorithm not only can use fewer nodes to effectively cover the monitoring area completely and improve the coverage of the network but also can optimize resource allocation and prolong the network lifetime. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3492